Glanzmann Thrombasthenia- A Case Report of a Rare Congenital Bleeding Disorder. - Verma, Sarnya; Chavan, Sanjay; Varma, Sarita; Suresha, Suresha; Mane, Shailaja (Journal of Neonatal Surgery, 2025)
Glanzmann Thrombasthenia, a rare inherited bleeding disorder, is characterised by recurrent mucocutaneous bleeding secondary to an abnormality in platelet function. Clinical presentations may range from trivial bruising, recurrent epistaxis or gingivitis, menorrhagia, to massive life-endangering bleeding episodes. While some patients may be managed with preventive measures and local antifibrinolytic therapies, others may require frequent hospitalisation for platelet and packed red blood cell transfusions. With early diagnosis and accurate supportive management, this disorder has a favorable prognosis. Here, we report a rare case of Glanzmann Thrombasthenia in a 12 years old female child who presented to us with recurrent episodes of epistaxis and gingival bleeding.